Pengaruh Kepemimpinan dan Pelatihan Terhadap Kinerja Karyawan Melalui Etos Kerja Pada PT. Bank Syariah Mandiri - Asdar Waris; Zulkahfi Zulkahfi; Safriadi Darmansyah; Ayu Sri Wahyuni; Zhulqarnain Zhulqarnain; Ainun Afrianti (CV. Ulil Albab Corp, 2024)
This research aims to examine the effect of leadership and training on employee performance through work ethic at PT Bank Syariah Mandiri in the Mamuju area office. The data in this research was obtained from employees at Bank Syariah Mandiri's Mamuju area office who were willing to be respondents.This research uses primary data by conducting direct research in the field by giving questionnaires/question sheets to 60 respondents. The data analysis method used is Structural Equation Model (SEM) analysis. The research results show that: leadership, training and work ethic variables have a positive and significant effect on employee performance. Leadership and training variables have a positive and significant effect on work ethic. Leadership and training variables have a positive and significant effect on employee performance through work ethic.